2000
DOI: 10.2302/kjm.49.26
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cerebral Microcirculation. Update.

Abstract: Abstract. The present symposium during Brain 99 was convened to explore the current aspects of the neural (extrinsic and intrinsic) and chemical control of the microvasculature in the brain with specific relevance to stimuli and rapid flow responses. N. Suzuki demonstrated the presence of neurokinin-1 receptors along the axons of vasoactive intestinal polypeptide-containing cerebrovascular para sympathetic nerves. Since the receptors were activated by substance P, calcitonin gene-related peptide and neurokinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Therefore, intracallosal blood vessels could be regulated primarily by neighboring neuronal elements (intracallosal neurons) and then by an integrated vascular mechanism, as proposed for other vascular beds in the CNS (Tomita et al, ). How and when intravascular SP gains access to intracallosal perivascular nNOS/NK1 neurons to induce NO release remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, intracallosal blood vessels could be regulated primarily by neighboring neuronal elements (intracallosal neurons) and then by an integrated vascular mechanism, as proposed for other vascular beds in the CNS (Tomita et al, ). How and when intravascular SP gains access to intracallosal perivascular nNOS/NK1 neurons to induce NO release remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
“…Stimulation of the sphenopalatine ganglion increases intracranial blood flow and induces vasodilation through the parasympathetic innervation in the intracranial blood vessels (Suzuki et al, 1991, Tomita et al, 2000, Ayajiki et al, 2005, Yarnitsky et al, 2005). Data in experimental models of stroke have demonstrated that stimulation of this ganglion increased blood flow, reduced infarct volume and improved functional outcomes (Henninger and Fisher, 2007, Bar-Shir et al, 2010).…”
Section: Collateral Circulation and Arteriogenesis As The New Thermentioning
confidence: 99%
“…For example, nitric oxide is a potent vasodilator of the cerebral circulation, but it has been hypothesized that this vasodilatory pathway is disrupted during ischemia as a result of PGHS-derived superoxide anions. 126 Further studies are necessary to decipher the complexity of these systems.…”
Section: Cerebral Blood Flow and Ischemiamentioning
confidence: 99%